1998
DOI: 10.1097/00006123-199802000-00038
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of an Antioxidant, Ebselen, in Patients with Delayed Neurological Deficits after Aneurysmal Subarachnoid Hemorrhage

Abstract: Ebselen reduced brain damage in patients with delayed neurological deficits after subarachnoid hemorrhage and may be a promising neuroprotective agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(130 citation statements)
references
References 35 publications
3
127
0
Order By: Relevance
“…The remaining 24 trials were included in the analysis, including 8,552 patients (Macdonald et al, 2008;Asano et al, 1996;Chou et al, 2008;Gomis et al, 2010;Haley et al, 1993Haley et al, , 1997Hop et al, 2000;Kassell et al, 1996;Ohman and Heiskanen, 1988;Petruk et al, 1988;Pickard et al, 1989;Saito et al, 1998;Shaw et al, 2000;Shibuya et al, 1992;Siironen et al, 2003;Juvela et al, 2005;Springborg et al, 2007;Suzuki et al, 1989;Tseng et al, 2009;van den Bergh et al, 2005van den Bergh et al, , 2006Westermaier et al, 2010;Wong et al, 2010Wong et al, , 2011. A total of 4,818 patients were randomized to pharmaceutical treatment, and 3,734 patients to placebo.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 24 trials were included in the analysis, including 8,552 patients (Macdonald et al, 2008;Asano et al, 1996;Chou et al, 2008;Gomis et al, 2010;Haley et al, 1993Haley et al, , 1997Hop et al, 2000;Kassell et al, 1996;Ohman and Heiskanen, 1988;Petruk et al, 1988;Pickard et al, 1989;Saito et al, 1998;Shaw et al, 2000;Shibuya et al, 1992;Siironen et al, 2003;Juvela et al, 2005;Springborg et al, 2007;Suzuki et al, 1989;Tseng et al, 2009;van den Bergh et al, 2005van den Bergh et al, , 2006Westermaier et al, 2010;Wong et al, 2010Wong et al, , 2011. A total of 4,818 patients were randomized to pharmaceutical treatment, and 3,734 patients to placebo.…”
Section: Resultsmentioning
confidence: 99%
“…For blinding, risk of bias was low in 20 studies (Macdonald et al, 2008;Asano et al, 1996;Gomis et al, 2010;Haley et al, 1993Haley et al, , 1997Hop et al, 2000;Kassell et al, 1996;Petruk et al, 1988;Pickard et al, 1989;Shaw et al, 2000;Shibuya et al, 1992;Siironen et al, 2003;Springborg et al, 2007;Tseng et al, 2009;van den Bergh et al, 2005van den Bergh et al, , 2006Westermaier et al, 2010;Wong et al, 2010), and unclear in four studies (Chou et al, 2008;Ohman and Heiskanen, 1988;Saito et al, 1998;Suzuki et al, 1989). High risk of bias was not observed in any of the studies.…”
Section: Risk Of Bias Assessmentsmentioning
confidence: 95%
See 2 more Smart Citations
“…Ebselen also mitigates the increase of serum ALT observed in alcohol-induced liver injury (Kono et al 2001). Ebselen possesses glutathione peroxidase-like action (Parnham et al 1988) and has been shown to be a potent neuroprotective agent during both stroke and subarachnoid haemorrhage in man (Saito et al 1998) and in animal models of neurodegenerative diseases (Dawson et al 1995;Takasago et al 1997). Membrane lipid peroxidation can induce damage, including transition in permeability and release of apoptotic factors that lead to cell death (Mattson 1998).…”
Section: Discussionmentioning
confidence: 99%